Perceived convenience as a driver of South African Generation Y consumers’ online repurchase intentions - Mbali B. Selemela; Dr Rita Klonaridis; Prof Heleneze T. Lues; Dr Chantel Muller (The Retail and Marketing Review)
The digital transformation and technological advancements resulting from the fourth industrial revolution (4IR), paired with other external factors including the ramifications of the COVID-19 pandemic, have led to the South African online retail market increasing by 66% in 2020 and surpassing a market value of R55 billion in 2022. While online shopping continues to increase steadily, reports of the factors impacting consumer repurchase intentions are vague in the literature, specifically from a consumer convenience perspective and in the South African context. As such, this study provides a departure point and employed the SERVCON (service convenience) model to investigate whether access, search, transaction, execution and post-service convenience had a statistically significant direct influence on South African Generation Y consumers’ online repurchase intentions. Following a descriptive research and cross-sectional design, this study collected quantitative data from 400 Generation Y university students, using a self-administered questionnaire. While all five factors were significant, access convenience had a negative impact and execution convenience had no statistically significant influence on repurchase intentions. Nonetheless, the findings will guide academic and industry stakeholders in understanding consumers’ perceived convenience and how to optimise every aspect accordingly.